2017
DOI: 10.3171/2016.9.peds16152
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of convection-enhanced delivery of liposomal doxorubicin to treat pediatric diffuse intrinsic pontine glioma and thalamic high-grade glioma

Abstract: OBJECTIVEPediatric high-grade gliomas (pHGGs) including diffuse intrinsic pontine gliomas (DIPGs) are primary brain tumors with high mortality and morbidity. Because of their poor brain penetrance, systemic chemotherapy regimens have failed to deliver satisfactory results; however, convection-enhanced delivery (CED) may be an alternative mode of drug delivery. Anthracyclines are potent chemotherapeutics that have been successfully delivered via CED in preclinical supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…We employed TSL similar to the formulation initially proposed by Needham et al. ( 2000 ), and loaded with the chemotherapy doxorubicin as this drug is effective against glioma in vitro (Stan et al., 1999 ; Veringa et al., 2013 ; Sewing et al., 2017 ), but cannot cross the BBB. To elicit localized brain hyperthermia, we employed an interstitial needle probe based on radiofrequency heating, inserted through skull burr holes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed TSL similar to the formulation initially proposed by Needham et al. ( 2000 ), and loaded with the chemotherapy doxorubicin as this drug is effective against glioma in vitro (Stan et al., 1999 ; Veringa et al., 2013 ; Sewing et al., 2017 ), but cannot cross the BBB. To elicit localized brain hyperthermia, we employed an interstitial needle probe based on radiofrequency heating, inserted through skull burr holes.…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin is currently not used in the treatment of brain tumors because it cannot cross the BBB, but is effective against high-grade gliomas in culture (Stan et al., 1999 ; Veringa et al., 2013 ; Sewing et al., 2017 ) and in vivo (Gong et al., 2011 ; Sewing et al., 2017 ), and also patient benefit has been demonstrated when administered in liposomal form (Fabel et al., 2001 ). Thus, proof of doxorubicin delivery across the BBB has potential therapeutic value, but would also demonstrate viability of the proposed approach in delivering drugs across the BBB that otherwise could not cross (Sewing et al., 2017 ). In addition, we wanted to examine long-term survival in large animals to evaluate the neurotoxicity of doxorubicin delivered to focal areas of the brain in the setting of transient hyperthermia, which has not been evaluated in prior studies.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, intratumoral delivery of TMZ has not been clinically tested yet but promising results have been presented in experimental brain tumor models and clinical trials also with other TMZ formulations or cytostatic drugs [31][32][33][34][35]. Other mechanisms of local drug administration have also been used.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, our group demonstrated the feasibility and safety of CED within the brainstem in a rodent model. 59 The safety and toxicity of potential therapeutic agents as well as the distribution pattern of the infusate have subsequently been studied in further animal studies 41,62,63,65,69,70,76,77 that have confirmed that CED does not cause relevant injury to the brainstem.…”
Section: Enhanced Drug Deliverymentioning
confidence: 99%